We don't want your water: Broadening community understandings of and engagement in flood risk and mitigation - Skilton, Liz; Osland, Anna C.; Willis, Emma; Habib, Emad H.; Barnes, Stephen R.; ElSaadani, Mohamed; Miles, Brian; Do, Trung Quang (Frontiers in Water, 2022)
Managers, community leaders, and the public frequently encounter communication barriers that hinder implementation of community flood mitigation despite opportunities to use new hydroinformatics tools to understand flood risk. Due to changing flood risk, communities across the USA will have an increased need to communicate with a variety of stakeholders about flood risk and mitigation. Lafayette, La., USA, having recently experienced a major flood event (the 2016 Louisiana Floods), is representative of other communities experiencing changes to flood impacts because of climatic changes, development, and other factors. Using focus groups, this study delves into better understanding the disconnect between individual and community perceptions of flood risks, and how emerging hydroinformatics tools can bridge these gaps. Our research demonstrates the need for scalable tools and technology that can illustrate local context, include local historical and simulated events at multiple levels of community impact, provide comprehensive community perspectives, and allow individuals to expand their knowledge beyond their homes, businesses, and places of work.